Rhabdomyomatous Mesenchymal Hamartoma: A Deep Subcutaneous Lesion in the Sternoclavicular Area. Issue 1 (January 2016) - Orozco‐Covarrubias, Luz; Carrasco‐Daza, Daniel; Diaz‐Noriega, Ana; Lara‐Mendoza, Leticia; Ruiz‐Maldonado, Ramon
Abstract: Cutaneous rhabdomyomatous mesenchymal hamartoma (RMH) is a rare benign tumor composed of two or more types of mesenchymal‐derived cells. RMHs are generally sporadic and independent, but they can be associated with congenital abnormalities. We report a subcutaneous case of RMH in the sternoclavicular area with two recurrences after complete surgical excision. The course is variable and can range from spontaneous resolution to repeated recurrences.